Prevalence of behavioral problems and related family functioning among middle school students in an eastern city of China. (27th July 2012) - Ma, Xiquan; Yao, Yuhong; Zhao, Xudong
Abstract Introduction This study was carried out to explore the prevalence of behavioral problems among adolescents in junior high school as well as their families' levels of function or dysfunction that contribute to children's behavioral problems in Mainland China. Methods One thousand, four hundred and seventy‐six adolescents (ages 12–17 years) and their families participated in the study. Parents completed a self‐administered questionnaire consisting of the Child Behavior Checklist (CBCL), Family Assessment Device (FAD) and a number of demographic questions. Student's t‐tests, chi‐square tests and stepwise multiple regression models were performed to examine the variables. Results The estimated prevalence of behavioral problems was 10.5% based on the cutoff point for behavioral problems according to the CBCL. Behavioral problems identified by the CBCL occurred differently at various developmental stages (F = 10.06, P = 0.007). The study showed that inappropriate affective responsiveness, poor affective involvement and low ability of problem solving in the family were significantly associated with increased risk for externalizing behavior problems and total behavior problems of boys. Inappropriate affective responsiveness and poor communication in the family were significantly associated with increased risk for internalizing problems for boys. Poorly established patterns of family behavior were important factors contributing to the development of externalizing behavior problems, internalizing behavior problems and total behavior problems for girls'. Discussion The present findings suggest that functional levels of family are associated with the adolescent's mental health, and that specific family dynamics may influence the development of behavioral problems among adolescents in China.